Protopine reduces the inflammatory activity of lipopolysaccharide-stimulated murine macrophages - Bae, Deok Sung; Kim, Young Hoon; Pan, Cheol-Ho; Nho, Chu Won; Samdan, Javzan; Yansan, Jamyansan; Lee, Jae Kwon (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2012)
Protopine is an isoquinoline alkaloid contained in plants in northeast Asia. In this study, we investigated whether protopine derived from Hypecoum erectum L could suppress lipopolysaccharide (LPS)-induced inflammatory responses in murine macrophages (Raw 264.7 cells). Protopine was found to reduce nitric oxide (NO), cyclooxygenase-2 (COX-2), and prostaglandin E-2 (PGE(2)) production by U'S-stimulated Raw 264.7 cells, without a cytotoxic effect. Pm-treatment of Raw 264.7 cells with protopine reduced the production of pro-inflammatory cytokines. These inhibitory effects were caused by blocking phosphorylation of mitogen-activated protein kinases (MAP kinases) and also blocking activation of a nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B). [BMB reports 2012; 45(2): 108-113]
Keywords: NITRIC-OXIDE; NUCLEAR-FACTOR; PHORBOL ESTER; KAPPA-B; EXPRESSION; CYTOKINES; INTERLEUKIN-1; INHIBITION; ALPHA; GENE